Sosialisasi CerMat Sebagai Implementasi Model Pembelajaran Matematika Berdasarkan Sistem Among Di SMPK Kesuma Cakranegara - Junaidi Junaidi; Harry Soeprianto (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
Devotion aims to overcome the problems found in the form of low student learning outcomes at Kesuma Cakranegara Junior High School. in addition, socialization activities as an initial alternative in improving the competence of teachers, especially in the pedagogical competence of mathematics teachers of Kesuma cakranegara Junior High School. The result is in the form of teacher awareness about the importance of student awareness in learning independently. Increasing teacher knowledge about CerMat as an Implementation of Mathematics Learning Model Based on Among System in SMPK Kesuma Cakranegar. With the awareness of teachers, the next activity can be done, namely lesson study to create a role model for CerMat-based learning teachers.